(untitled) (Scientific journal of the Fergana State University, 2024)
The author continues to consider the methods of updating precedent texts in intertextual headings of the press, which he began in the publication of this bulletin “Formal actualization of precedent texts in intertextual headings of the press” (2023, No. 2, p. 800-803). This article is devoted to semantic ways of transforming a precedent text – based on polysemy, antonymy, homonymy, paronymy and paronomasia.